Lycopene in cancer prevention - Şahin, Kazım; Küçük, Ömer (Springer Berlin Heidelberg, 2013)
Lycopene, a red-colored carotenoid, present in many fruits and vegetables, including tomatoes and their processed products, watermelon, guava, carrots, pink grapefruit, and sweet potatoes, is inversely associated with the risk of many cancers. Unlike beta-carotene, lycopene lacks a beta-ionone ring and therefore has no provitamin A activity. However, the 11 conjugated and two nonconjugated double bonds in lycopene make it highly reactive toward oxygen and free radicals. Lycopene has been proposed to protect against cancer through various properties including decreased lipid oxidation, inhibition of cancer cell proliferation, and most notably potent antioxidant properties, apoptosis, increased gap-junctional communication, interferences in insulin-like growth factor 1 receptor signaling pathways, and cell cycle progression. Preclinical studies and clinical trials show that lycopene has potent in vitro and in vivo antitumor effects, suggesting potential preventive and therapeutic roles for lycopene. Further mechanistic studies and randomized controlled clinical intervention trials with lycopene in cancer patients are warranted. In this chapter, cancer prevention using lycopene is reviewed and the possible mechanisms of action are described. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: Cancer; Lycopene; Molecular mechanism; Nutrition; Prevention